2014
DOI: 10.1007/s12013-014-0084-4
|View full text |Cite
|
Sign up to set email alerts
|

Polar Profile of Antiviral Peptides from AVPpred Database

Abstract: Diseases of viral origin in humans are among the most serious threats to health and the global economy. As recent history has shown the virus has a high pandemic potential, among other reasons, due to its ability to spread by air, hence the identification, investigation, containment, and treatment of viral diseases should be considered of paramount importance. In this sense, the bioinformatics research has focused on finding fast and efficient algorithms that can identify highly toxic antiviral peptides and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…It was observed that some properties like helix initiation parameter (c), frequency of C‐terminal non beta region (d), free energy in beta‐strand region (e, m) and frequency of helix (f, k) were more discriminative compared to others. Similar results were reported by Chang and Yang and Polanco et al while analyzing the physicochemical properties of AVPs.…”
Section: Resultssupporting
confidence: 90%
“…It was observed that some properties like helix initiation parameter (c), frequency of C‐terminal non beta region (d), free energy in beta‐strand region (e, m) and frequency of helix (f, k) were more discriminative compared to others. Similar results were reported by Chang and Yang and Polanco et al while analyzing the physicochemical properties of AVPs.…”
Section: Resultssupporting
confidence: 90%
“…The distribution of relative frequencies of the described groups indicates that the inflection points do not match in the groups. This has been already observed for other peptide and protein groups (Polanco et al, 2012;2013;2013a;2014a;2014b;2014c;2014d;2014e). We assume that their location is the identifier underlying the measurement of the electromagnetic balance of a protein.…”
Section: Discussionmentioning
confidence: 73%
“…In order to deepen the characterization of proteins associated with Mycobacterium tuberculosis strains on the basis of their physico-chemical properties, we calibrated the mathematical-computational Polarity Index Method (PIM) (Polanco et al, 2012), with all proteins associated with Mycobacterium tuberculosis virulence pathway (MTVP) group from the Tuberculist Database (Lew et al, 2011). The PIM is a supervised method that we used for the identification and characterization of various peptide and protein groups based on the linear representation of the protein (Polanco et al, 2012;2013;2013a;2014a;2014b;2014c;2014d;2014e). Its metric considers only polarity as a physico-chemical property, and it is based on a polar matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In order to deepen the understanding of this important group of cargo-proteins specialized in the transport of lipids, we applied the supervised computational tool called Polarity index method (Polanco et al, 2012), which has already been used in the analysis of other groups of peptides and proteins (Polanco & Samaniego, 2009;Polanco et al, 2012;2013;2013a;2014a;2014b;2014c;2014d;2014e). Here, this technique was used to characterize Chylomicrons, VLDLs, IDLs, LDLs, HDLs, and Atherosclerosis, i.e.…”
Section: Introductionmentioning
confidence: 99%